A ceramic capacitor with a protective layer and a method for manufacturing the same
Patent Information
- Application Number
- CN202611087669.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-22
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2046-07-22
AI Technical Summary
[0008]本发明的目的在于解决现有技术中陶瓷电容器抗应力变化能力差、使用过程中易引起啸叫从而影响使用的技术问题,具体提供一种含保护层的陶瓷电容器及其制备方法
本发明通过在陶瓷主体外部设置含中空微球的复合保护层,利用中空微球的空心结构赋予保护层较低的弹性模量和良好的压缩变形能力,使得当陶瓷主体受到外部碰撞、刮擦、按压或PCB板弯曲产生的应力时,中空微球能够通过自身形变吸收和分散应力能量,避免应力集中传递至陶瓷主体内部,有效降低了陶瓷主体开裂的风险,显著提升了MLCC元件的抗外部应力能力。
Smart Images

Figure CN122599278B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of ceramic capacitor preparation methods, and relates to a ceramic capacitor with a protective layer and its preparation method. Background Technology
[0002] Multilayer ceramic capacitors (MLCCs) have advantages such as small size, large capacitance, low equivalent resistance, and good high-frequency characteristics, and are widely used in consumer electronics, communication equipment, automotive electronics, and industrial control. However, as electronic devices develop towards miniaturization, high integration, and high power density, the mechanical reliability and acoustic noise issues faced by MLCCs during use are becoming increasingly prominent.
[0003] In applications where quiet operation is crucial, such as smartphones, laptops, power management modules, and electric vehicles, the acoustic noise generated by MLCCs during operation, also known as howling, has become a key technical bottleneck restricting their further application. When an MLCC is working, the ceramic dielectric inside it undergoes electrostriction under an alternating electric field, causing minute, periodic deformations in the ceramic body. When the frequency of this deformation falls within the audible range, the deformation is transmitted through the solder joints to the printed circuit board, exciting the PCB to resonate and radiating audible noise outwards—the howling phenomenon.
[0004] Invention patent CN121790170A discloses a ceramic capacitor and its preparation method. Specifically, a buffer layer with a periodic corrugated structure is set in the protected area of the ceramic body. The buffer layer is located between the first cover plate and the second cover plate. It uses the arch effect to decompose the external bending pressure or welding stress into dispersed stress along the tangent direction of the arch, so that it is transmitted to both sides along the waveform, thereby reducing the risk of stress damage to the effective electrode area and improving the bending resistance of the ceramic capacitor.
[0005] However, after practical use, the above solution has limited effect on improving the bending resistance of capacitors. During the sintering process, the bending layer in the block is prone to cracking due to the different coefficients of thermal expansion, which affects the yield. At the same time, the above solution has also failed to achieve the expected effect in suppressing the squealing phenomenon.
[0006] In addition, existing technologies have also attempted to suppress whistling by coating the outside of MLCCs with organic resin or by using rubber bases during installation. However, organic coatings usually have problems such as poor heat resistance, low bonding strength with the ceramic body, and complex manufacturing processes, while rubber bases increase device size and cost, which is not conducive to miniaturization.
[0007] In view of this, how to endow MLCCs with good dynamic vibration damping capabilities without significantly sacrificing their existing bending resistance, thereby effectively suppressing howling noise under alternating electric fields, and further improving their ability to resist random stresses such as external collisions, scratches, and pressure, is a technical problem that urgently needs to be solved by those skilled in the art. Summary of the Invention
[0008] The purpose of this invention is to solve the technical problems of poor stress resistance and whistling during use of ceramic capacitors in the prior art, which affect their use. Specifically, this invention provides a ceramic capacitor with a protective layer and its preparation method.
[0009] To achieve the above objectives, the present invention proposes the following technical solution: In the first aspect, a ceramic capacitor with a protective layer is proposed, comprising: A ceramic body, the ceramic body including an effective electrode region; wherein, the effective electrode region includes a plurality of inner electrode layers and a plurality of dielectric ceramic layers, the inner electrode layers and the dielectric ceramic layers being alternately stacked; Two external electrodes are respectively disposed on two opposite end faces of the ceramic body along the length direction and are electrically connected to the corresponding internal electrode layers. The ceramic capacitor also includes a composite protective layer that covers the entire outer surface area of the ceramic body except for the two end faces. The composite protective layer comprises dispersed hollow microspheres.
[0010] Furthermore, the hollow microspheres are hollow glass microspheres or hollow ceramic microspheres; The hollow microspheres have a closed or semi-closed cavity structure inside.
[0011] Furthermore, the particle size of the hollow microspheres is 1~150μm.
[0012] Furthermore, the bulk density of the hollow microspheres is 0.06~0.50 g / cm³. 3 .
[0013] Furthermore, the true density of the hollow microspheres is 0.1~1.5 g / cm³. 3 .
[0014] Furthermore, the thickness of the composite protective layer is 5~200μm.
[0015] Furthermore, the thickness of the composite protective layer is h, and the thickness of the ceramic body in the stacking direction is H, satisfying: 0.02≤h / H≤0.15.
[0016] Secondly, a method for preparing a ceramic capacitor with a protective layer is proposed, comprising the following steps: S11. Take a sintered and chamfered ceramic body. The ceramic body includes an effective electrode region. The effective electrode region includes several inner electrode layers and several dielectric ceramic layers. The inner electrode layers and the dielectric ceramic layers are stacked alternately. S12. Prepare a protective slurry containing hollow microspheres; S13. The protective slurry is applied to all the outer surface areas of the ceramic body except for the two end faces and dried to form a protective layer. S14. Perform a first heat treatment on the protective layer to obtain a ceramic body containing a composite protective layer; S15. Apply an external electrode paste to the area where the two end faces of the ceramic body are located, and form an external electrode after a second heat treatment, thereby obtaining a ceramic capacitor with a protective layer. Wherein, the temperature of the first heat treatment is higher than the temperature of the second heat treatment, and the temperature of the first heat treatment is lower than the sintering temperature of the ceramic body in S11.
[0017] Thirdly, another method for preparing a ceramic capacitor with a protective layer is proposed, including the following steps: S21. Take a sintered and chamfered ceramic body. The ceramic body includes an effective electrode region. The effective electrode region includes several inner electrode layers and several dielectric ceramic layers. The inner electrode layers and the dielectric ceramic layers are stacked alternately. S22. Prepare a protective slurry containing hollow microspheres; S23. Apply external electrode paste to the areas where the two end faces of the ceramic body are located and dry it; S24. The protective slurry is applied to all the outer surface areas of the ceramic body except for the two end faces and dried to form a protective layer. S25. Perform a third heat treatment on the ceramic body containing the protective layer and the external electrode paste to obtain a ceramic capacitor with a protective layer. The temperature of the third heat treatment is lower than the sintering temperature of the ceramic body in S21.
[0018] Furthermore, the step of preparing the protective slurry includes: Hollow microspheres and matrix material are added to an organic solvent to form a first mixed system; an additive is added to the first mixed system to form a second mixed system; the second mixed system is ultrasonically stirred in a water bath at 50℃~70℃ for 4~6 hours to form a uniform slurry. The volume ratio of the hollow microspheres to the matrix material is (3.7~17):3; The volume ratio of the total volume of the hollow microspheres and the matrix material to the volume of the organic solvent is 3:(5~6); The amount of the additive is 40% of the mass of the organic solvent, and the additive is selected from one or more of binders, plasticizers, stabilizers, defoamers, and dispersants.
[0019] The beneficial effects of this invention are: This invention provides a composite protective layer containing hollow microspheres on the outside of a ceramic body. The hollow structure of the microspheres gives the protective layer a low elastic modulus and good compressive deformation capacity. When the ceramic body is subjected to stress from external impacts, scratches, pressure, or bending of the PCB board, the hollow microspheres can absorb and disperse the stress energy through their own deformation, preventing stress concentration from being transmitted to the interior of the ceramic body. This effectively reduces the risk of cracking of the ceramic body and significantly improves the resistance of MLCC components to external stress.
[0020] This invention provides a composite protective layer containing hollow microspheres on the outside of a ceramic body. The hollow structure of the microspheres has excellent vibration damping characteristics. When the MLCC element generates inverse piezoelectric vibration under the action of an alternating electric field, the hollow microspheres in the composite protective layer convert the vibration mechanical energy into heat energy through friction and deformation of the cavity wall, thereby significantly reducing the transmission of vibration energy to the PCB board and significantly reducing the howling noise, specifically as low as 33dB, which effectively suppresses howling noise compared to existing technologies.
[0021] The composite protective layer provided by this invention covers at least the outer surface area of the ceramic body corresponding to the effective electrode area. The effective electrode area is the key path for crack propagation and vibration transmission. By protecting this area in a targeted manner, the extension path of cracks and the transmission channel of vibration are blocked from the source.
[0022] This invention provides a distributed sintering process and, based on that, a co-firing scheme, which simultaneously sintersects the protective layer and the outer electrode in the same heat treatment step. While maintaining the integrity of the hollow microsphere structure, this significantly simplifies the process and reduces production costs. Although its overall performance is slightly lower than that of the step-firing scheme, it is still far superior to conventional MLCCs without a protective layer in the prior art, providing a flexible technical option for different production conditions and cost budgets.
[0023] The preparation method of the present invention can be achieved by adding coating and heat treatment processes to the existing MLCC production line without major modifications to the main process. It has good compatibility with existing processes and is easy to promote and apply. At the same time, the processing cost is low. The main material of the composite protective layer, hollow glass microspheres, is a recycled product of industrial waste, which is inexpensive. The amount used is relatively small compared to the overall MLCC production line, and the material and preparation costs are relatively controllable.
[0024] It should be understood that all combinations of the foregoing concepts and the additional concepts described in more detail below can be considered part of the inventive subject matter of this disclosure, provided that such concepts do not contradict each other. Attached Figure Description
[0025] The accompanying drawings are not drawn to scale. In the drawings, each identical or nearly identical component shown in the various figures can be denoted by the same reference numeral. For clarity, not every component is labeled in each figure. Embodiments of various aspects of the invention will now be described by way of example and with reference to the accompanying drawings. The embodiments in the drawings do not constitute any limitation on the invention. Other drawings can be obtained by those skilled in the art based on the following drawings without inventive effort, wherein: Figure 1 This is a schematic cross-section of the ceramic capacitor in an embodiment of the present invention. Figure 1 ; Figure 2 This is a schematic cross-section of the ceramic capacitor in an embodiment of the present invention. Figure 2 ; Figure 3 This is a front view of the ceramic body in an embodiment of the present invention; Figure 4 This is a three-dimensional schematic diagram of the ceramic body in an embodiment of the present invention.
[0026] Legend: 1. Composite protective layer; 2. External electrode; 3. Internal electrode layer; 4. Dielectric ceramic layer; 101. First main surface; 102. First end face; 103. Second end face; 104. First side face; 105. Second side face. Detailed Implementation
[0027] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the described embodiments of the present invention without creative effort are within the scope of protection of the present invention. Unless otherwise defined, the technical or scientific terms used herein should have the ordinary meaning understood by those skilled in the art.
[0028] The terms "first," "second," and similar words used in the specification and claims of this patent application do not indicate any order, quantity, or importance, but are merely used to distinguish different components. Similarly, unless the context clearly indicates otherwise, the singular forms of "an," "a," or "the," etc., do not indicate a quantity limitation, but rather indicate the presence of at least one. Terms such as "comprising" or "including" indicate that the element or object preceding "comprising" encompasses the features, wholes, steps, operations, elements, and / or components listed following "comprising" or "including," and do not exclude the presence or addition of one or more other features, wholes, steps, operations, elements, components, and / or sets thereof. Terms such as "upper," "lower," "left," and "right" are used only to indicate relative positional relationships; when the absolute position of the described object changes, the relative positional relationship may also change accordingly.
[0029] This invention discloses a ceramic capacitor, comprising: a ceramic body, two external electrodes 2, and a composite protective layer 1.
[0030] The ceramic body includes an effective electrode region; wherein the effective electrode region includes several inner electrode layers 3 and several dielectric ceramic layers 4, and the inner electrode layers 3 and dielectric ceramic layers 4 are stacked alternately.
[0031] Two external electrodes 2 are respectively disposed on two opposite end faces of the ceramic body along the length direction, and are electrically connected to the corresponding internal electrode layers 3.
[0032] The composite protective layer 1 covers the entire outer surface area of the ceramic body except for the two end faces.
[0033] In this invention, the effective electrode region refers to the area defined by the portion of each inner electrode layer 3 and its adjacent dielectric ceramic layer 4 facing each other in the stacking direction after multiple inner electrode layers 3 and dielectric ceramic layers 4 are alternately stacked; that is, the spatial range enclosed by the outer boundary of the overlapping area of the inner electrode layer 3 and dielectric ceramic layer 4. The effective electrode region is the main area for generating capacitance in MLCCs, and its projected area on the outer surface is the effective area for generating capacitance.
[0034] For details, see attached. Figure 3-4 As shown, the ceramic body has a roughly rectangular parallelepiped structure, having a first main surface 101 and a second main surface, i.e., an upper surface and a lower surface, arranged opposite to each other in the stacking direction; a first end face 102 and a second end face 103 arranged opposite to each other in the length direction, i.e. the left-right direction; and a first side face 104 and a second side face 105 arranged opposite to each other in the width direction, i.e. the vertical direction.
[0035] Specifically, the first main surface 101, i.e. the upper surface, is the main plane located at the top in the stacking direction; the second main surface, i.e. the lower surface, is the main plane opposite to the first main surface 101 in the stacking direction; the first end face 102 is the plane located at the left end in the length direction; the second end face 103 is the plane located at the other end, i.e. the right end, opposite to the first end face 102 in the length direction; the first side face 104 is the plane located on the top side in the width direction; and the second side face 105 is the plane located on the other side, i.e. the bottom side, opposite to the first side face 104 in the width direction.
[0036] The composite protective layer 1 covers all outer surfaces of the ceramic body except for the first end face 102 and the second end face 103, that is, it covers the first main surface 101, the second main surface, the first side surface 104, and the second side surface 105. The first end face 102 and the second end face 103 are the surfaces that expose the ends of the inner electrode layer 3. The two outer electrodes 2 are respectively disposed on the first end face 102 and the second end face 103 and are electrically connected to the exposed ends of the inner electrode layer 3.
[0037] In this embodiment, the composite protective layer 1 covers the corresponding areas of the first main surface 101, the second main surface, the first side surface 104, and the second side surface 105, that is, the other four surfaces excluding the two end faces where the outer electrode 2 is located.
[0038] The composite protective layer 1 comprises dispersed hollow microspheres; the composite protective layer 1 also includes a matrix material in which the hollow microspheres are dispersed.
[0039] Specifically, hollow microspheres are uniformly distributed in the composite protective layer 1 in the form of discrete phases, and adjacent microspheres are separated by a matrix material.
[0040] Among them, hollow microspheres are hollow glass microspheres or hollow ceramic microspheres; both hollow glass microspheres and hollow ceramic microspheres have closed or semi-closed cavity structures inside.
[0041] The hollow microspheres described above have a particle size of 1~150 μm and a bulk density of 0.06~0.50 g / cm³. 3 The true density is 0.1~1.5 g / cm³. 3 .
[0042] Specifically, the particle size of hollow microspheres affects their dispersion state in the matrix, interfacial bonding area, and deformation behavior under stress. Smaller particle sizes result in a larger interfacial bonding area between the microsphere and the matrix, leading to higher stress transfer efficiency and facilitating more uniform distribution of external impact loads throughout the protective layer. Larger microspheres have thicker walls and higher compressive strength, exhibiting primarily elastic deformation under stress and capable of repeatedly absorbing stress energy. However, their smaller interfacial bonding area with the matrix limits their stress dispersion effect.
[0043] The bulk density and true density of hollow microspheres together determine the overall density and porosity of the composite protective layer 1. The bulk density reflects the filling efficiency of the microspheres in their natural packing state, affecting the rheology and coating uniformity of the protective slurry. The true density directly reflects the cavity ratio of the microspheres. When the difference between the true density and the bulk density is greater, the cavity volume ratio of the microspheres is higher, the overall density of the protective layer is lower, the elastic modulus is smaller, and the buffering effect on external stress and the ability to dissipate vibration energy are stronger.
[0044] The aforementioned particle size range ensures that the hollow microspheres are uniformly dispersed in the matrix material, while also providing sufficient wall thickness to resist breakage during processing, thereby forming a stable and continuous cavity structure in the composite protective layer 1.
[0045] The thickness of composite protective layer 1 is 5~200μm.
[0046] In this application, the thickness of the composite protective layer 1 can be selected according to the size specifications of the capacitor. For 0603 specifications, the protective layer thickness is preferably 10μm to 30μm; for 0805 specifications, it is preferably 20μm to 50μm; for 1206 specifications, it is preferably 30μm to 100μm; and for 1210 and above specifications, it is preferably 50μm to 150μm. By limiting the thickness of the composite protective layer 1 within the above-mentioned range, it is ensured that it can effectively absorb stress and suppress howling, while also meeting the requirements for device miniaturization and capacitance density.
[0047] Preferably, the thickness of the composite protective layer 1 is h, the thickness of the ceramic body in the stacking direction is H, and satisfies: 0.02≤h / H≤0.15; the thickness of the external electrode 2 is less than the thickness of the composite protective layer 1.
[0048] Specifically, in high-temperature processes such as reflow soldering, the stress generated by the thermal expansion of the external electrode 2 is transmitted to the composite protective layer 1 and the ceramic body through the interface. If the thickness of the external electrode 2 is too large, its expansion will increase accordingly, and the stress concentration at the interface can easily lead to cracking of the composite protective layer 1 or cracks in the ceramic body. By controlling the thickness of the external electrode 2 to be less than the thickness of the composite protective layer 1, the composite protective layer 1 can act as a stress buffer layer, effectively absorbing and dispersing the interface stress generated by the expansion of the external electrode 2, thereby improving the thermal shock resistance reliability of the device.
[0049] See attached document Figure 1 As shown in the figure, an embodiment of the present invention discloses a method for preparing a ceramic capacitor, comprising the following steps: S11. Take the sintered and chamfered ceramic body. The ceramic body includes an effective electrode area. The effective electrode area includes several inner electrode layers 3 and several dielectric ceramic layers 4. The inner electrode layers 3 and dielectric ceramic layers 4 are stacked alternately.
[0050] In this embodiment, the preparation method of the ceramic body adopts existing technical means, specifically as follows: barium titanate formulation is added to a mixed solvent of toluene and ethanol, PVB binder, plasticizer and stabilizer are added, and zirconia balls are used as the dispersion medium. After ball milling, a stable slurry is obtained. After vacuum degassing of the slurry, a green film is prepared by casting. Nickel electrode slurry is printed onto the green film. After lamination and isostatic pressing, an MLCC green film with an electrode layer is formed. The green blank is cut, debinded, sintered at high temperature in a reducing atmosphere, and chamfered to obtain the ceramic body.
[0051] In this embodiment, the barium titanate-based formulation powder meets the condition that the content value change rate is ≤±15% within the range of -55℃ to 125℃; the mixed solvent is a mixed solution of toluene and ethanol at a volume ratio of 3:7; the dispersant is triethanolamine; and the plasticizer is dibutyl phthalate. The amount of PVB binder added is 8% to 15% of the mass of the barium titanate formulation. The above mixture is placed in a ball mill and ball-milled for 12 to 24 hours to obtain a uniformly dispersed media slurry. In the media slurry, the weight ratio of ceramic powder, solvent, and binder is approximately (50 to 70):(20 to 40):(5 to 15), and the solid content is 40% to 55%.
[0052] In this embodiment, the nickel electrode slurry is prepared using existing technology. Specifically, the method involves weighing 45-55 wt% nickel powder, 5-15 wt% inorganic ceramic additives, 2-4 wt% polymer resin, and 26-48 wt% organic solvent by weight percentage, and mixing them uniformly using a three-roll mill to form the nickel internal electrode slurry. The inorganic ceramic additive is barium titanate, and the organic solvent is at least one of terpineol or diethylene glycol butyl ether acetate. The nickel powder particle size is ≤1 μm.
[0053] S12. Prepare a protective slurry containing hollow microspheres. The steps for preparing the protective slurry include: Hollow microspheres and matrix materials are added to an organic solvent to form a first mixed system; Add an auxiliary agent to the first mixture to form a second mixture; The second mixture was ultrasonically stirred in a water bath at 50℃~70℃ for 4~6 hours to form a uniformly dispersed protective slurry. The power and frequency of the ultrasonic stirring should be such that the hollow microspheres are uniformly suspended without significant sedimentation.
[0054] The matrix material mentioned above is at least one of glass powder and ceramic precursor. In this embodiment, low-temperature glass powder is used.
[0055] The volume ratio of hollow microspheres to matrix material is (3.7~17):3.
[0056] Specifically, if there are too many hollow microspheres, unsealed pores will form between the hollow microspheres, thereby reducing the noise reduction effect; if there are too few hollow microspheres, the density of the covering layer will increase, reducing the noise dispersion effect and also reducing the noise reduction effect.
[0057] The volume ratio of the total volume of the hollow microspheres and the matrix material to the volume of the organic solvent is 3:(5~6), preferably, the volume ratio of the total volume of the hollow microspheres and the matrix material to the volume of the organic solvent is 1:2.
[0058] The amount of additive is 40% of the mass of the organic solvent, wherein the organic solvent is a mixed solution of toluene and ethanol, with a volume ratio of toluene to ethanol of 3:7. When the density of the organic solvent is 0.8 g / cm³... 3 At that time, the amount of additives used is 15% of the total mass of hollow microspheres and matrix materials.
[0059] The additives are selected from one or more of the following: binders, plasticizers, stabilizers, defoamers, and dispersants.
[0060] In this embodiment, the additives include binder, plasticizer, stabilizer, defoamer, and dispersant, wherein the weight ratio of binder, plasticizer, stabilizer, defoamer, and dispersant is (9~10):2:2:1:1; preferably, the weight ratio of binder, plasticizer, stabilizer, defoamer, and dispersant is 9.4:2:2:1:1.
[0061] Preferably, the adhesive is selected from at least one of PVB and ethyl cellulose; PVB is used in the examples.
[0062] Preferably, the plasticizer is selected from at least one of phthalic acid compounds, dibutyl phthalate, or adipate compounds, wherein the phthalic acid compound can be selected as DOP, and the adipate compound can be selected as diethyl adipate, and dibutyl phthalate is used in the examples.
[0063] Preferably, the stabilizer is polyethylene glycol.
[0064] Preferably, the defoamer is selected from at least one of n-butanol and siloxane; n-butanol is used in the examples.
[0065] Preferably, the dispersant is selected from at least one of phosphate ester dispersants and polycarboxylic acid dispersants; in the examples, phosphate ester dispersants are used.
[0066] S13. Apply the protective slurry to all outer surface areas of the ceramic body except for the two end faces and dry it to form a protective layer.
[0067] Specifically, the ceramic body is placed in an oven and dried at 80°C for 30 minutes to remove organic solvents, and then dried at 120°C for 2 hours.
[0068] S14. Perform a first heat treatment on the above protective layer to obtain a ceramic body containing the composite protective layer 1.
[0069] The above steps allow the media material such as glass powder in the protective slurry to melt and form a glass matrix, while the hollow microspheres are uniformly dispersed in the glass matrix and firmly bonded to the surface of the ceramic body to form a composite protective layer 1.
[0070] S15. Apply an external electrode paste to the area where the two end faces of the ceramic body are located, and form an external electrode 2 after a second heat treatment, thereby obtaining a ceramic capacitor with a protective layer.
[0071] In this embodiment, the external electrode paste is prepared using existing technology. Specifically, the method involves weighing 65-85 wt% silver powder, 2-6 wt% glass powder, 2-8 wt% polymer resin, and 4-16 wt% organic solvent by weight percentage, and mixing them uniformly using a three-roll mill to form the external electrode paste. The glass powder is borosilicate glass or zinc borosilicate glass, and the organic solvent is terpineol or diethylene glycol butyl ether acetate. The viscosity of the external electrode paste at 25°C is 10-50 Pa·s, and the solid content is 70-85 wt%.
[0072] The aforementioned external electrode slurry is applied to the areas at both ends of the ceramic body that are not covered with a protective layer by immersion. The immersion time is 1 to 5 seconds and the immersion depth is 0.2 to 0.5 mm. Subsequently, the external electrode 2 is formed by a second heat treatment.
[0073] Specifically, the temperature of the first heat treatment is higher than the temperature of the second heat treatment, and the temperature of the first heat treatment is lower than the sintering temperature of the ceramic body in S11 above.
[0074] The temperature of the first heat treatment is 900℃~1100℃, the temperature of the second heat treatment is 800℃~900℃, and the sintering temperature of the ceramic body in S11 is 1100℃~1350℃.
[0075] Specifically, during the first heat treatment, the temperature is first increased to 240℃ at a heating rate of 2℃ / min and held for 2 hours. Then, the temperature is increased to 350℃ at a heating rate of 1℃ / min and held for 2 hours. Next, the temperature is increased to 500℃ at a heating rate of 2℃ / min and held for 1 hour to remove binders and other additives. Finally, the temperature is increased to 900℃~1100℃ at a heating rate of 5℃ / min and held for 1 hour, and then allowed to cool naturally to room temperature.
[0076] The above preparation method involves sintering the composite protective layer 1 and the external electrode 2 in separate steps. Specifically, the composite protective layer 1 needs to be sintered at a sufficiently high temperature to allow the matrix materials, such as low-temperature glass powder, to fully melt and form a dense glass matrix. Simultaneously, this ensures that the hollow microspheres are firmly bonded to the matrix material and form chemical bonds with the surface of the ceramic substrate. This densed composite protective layer 1 possesses high mechanical strength and adhesion, effectively transferring and dispersing stress while ensuring the uniform and stable distribution of the hollow microspheres within the matrix.
[0077] The low-temperature sintering of the external electrode 2 is carried out after the composite protective layer 1 has been densified and solidified. Since this temperature is much lower than the sintering temperature of the composite protective layer 1, it will not damage the already formed structure of the composite protective layer 1, thereby avoiding situations such as collapse of the hollow microspheres, cracking of the protective layer, or peeling off from the ceramic body. At the same time, the external electrode 2 uses low-temperature sintering silver paste, which can be fully sintered at this temperature to obtain good conductivity and adhesion.
[0078] The aforementioned stepwise sintering preparation method allows for independent optimization of the material selection and process parameters of the composite protective layer 1 and the external electrode 2. Specifically, the composite protective layer 1 can be a glass system with a higher softening point, achieving better density and bonding strength at higher temperatures; the external electrode can be pure silver paste or silver-palladium paste, sintered at lower temperatures to avoid oxidation. This process flexibility makes the stepwise sintering scheme superior in overall performance.
[0079] In the aforementioned stepwise sintering process, the composite protective layer 1 covers the entire outer surface of the ceramic body except for the reserved electrode areas at both ends, with the width of the reserved electrode areas being 0.2mm~0.5mm. The outer electrode 2 covers both end faces of the ceramic body and partially extends to the top and bottom surfaces of the reserved electrode areas. There is a clear boundary between the extended edge of the outer electrode 2 and the edge of the composite protective layer 1. Because the composite protective layer 1 undergoes a first heat treatment to form a dense glass matrix, and the outer electrode 2 undergoes a second heat treatment, the sintering temperatures of the two are significantly different. The glass components in the outer electrode slurry will not undergo melting and interdiffusion with the sintered protective layer, thus the interface is clearly distinguishable.
[0080] See attached document Figure 2 As shown in the figure, this invention also discloses a method for preparing a ceramic capacitor, comprising the following steps: S21. Take a sintered and chamfered ceramic body. The ceramic body includes an effective electrode region, which includes several inner electrode layers 3 and several dielectric ceramic layers 4, with the inner electrode layers 3 and dielectric ceramic layers 4 stacked alternately. The specific preparation method is as described above.
[0081] S22. Prepare a protective slurry containing hollow microspheres, the specific preparation method of which is as described above.
[0082] S23. Apply external electrode paste to the two end faces of the ceramic body and dry it. The specific preparation method is as described above.
[0083] S24. Apply the protective slurry to all outer surface areas of the ceramic body except for the two end faces and dry it to form a protective layer. The specific preparation method is as described above.
[0084] S25. Perform a third heat treatment on the ceramic body containing the protective layer and the external electrode paste to obtain a ceramic capacitor with a protective layer.
[0085] Specifically, the temperature of the third heat treatment is lower than the sintering temperature of the ceramic body in S21.
[0086] The third heat treatment mentioned above, namely the co-firing temperature, is 650℃~900℃.
[0087] The above preparation method sintersects the composite protective layer 1 and the external electrode 2 simultaneously in the same heat treatment step. Specifically, the co-firing method combines the curing of the composite protective layer 1 and the sintering of the external electrode 2 into a single heat treatment, simplifying the process and improving production efficiency. During the co-firing process, the low-temperature glass powder in the protective slurry melts to form a matrix, while the silver particles in the external electrode slurry sinter and connect to form a conductive network. Both processes are completed synchronously within the same temperature window.
[0088] The aforementioned co-firing temperature ensures that the low-temperature glass powder can fully soften, flow, and form a continuous matrix, while the silver paste can be fully sintered to achieve good conductivity. Too low a co-firing temperature will result in incomplete curing of the composite protective layer 1 or insufficient sintering of the external electrode 2; too high a co-firing temperature may lead to the collapse of the hollow microspheres or over-sintering of the silver electrode.
[0089] The co-firing method described above requires only one heat treatment, resulting in a shorter process flow, lower energy consumption, and higher production efficiency. For manufacturing scenarios with large-scale production and high cost sensitivity, the co-firing approach offers significant economic advantages. Furthermore, the co-firing method creates an integrated interface between the composite protective layer 1 and the external electrode 2, reducing thermal stress between them and improving the long-term reliability of the product.
[0090] In the aforementioned co-firing process, the composite protective layer 1 covers the entire outer surface of the ceramic body except for the reserved electrode areas at both ends, and the outer electrode 2 covers the end faces of both ends of the ceramic body and extends partially to the top and bottom surfaces of the reserved electrode areas. Since the composite protective layer 1 and the outer electrode 2 are sintered simultaneously, the glass components at their interface partially melt and mix, forming a gradual fusion interface. This fusion interface helps to improve the bonding strength between the protective layer and the outer electrode 2 and reduce interface stress.
[0091] The ceramic capacitor, its preparation method, and its applications disclosed in this invention will be further described in detail below with reference to specific embodiments. Unless otherwise specified, the reagents and materials used in the examples and comparative examples are commercially available.
[0092] Example 1 A method for preparing a ceramic capacitor includes the following steps: S1. Take the sintered and beveled ceramic body, and the specific steps are as follows: (1) Ceramic slurry preparation: Barium titanate-based formulation powder with a dielectric constant of about 4200 and a temperature coefficient of X7R is selected, and mixed with organic solvent, dispersant and binder. The mixture is then dispersed evenly by ball milling to prepare the medium slurry.
[0093] Specifically, 15g of PVB binder was dissolved in 100mL of a mixed solvent of toluene and ethanol in a volume ratio of 3:7, and stirred until completely dissolved; 100g of barium titanate-based X7R formulation powder, 2g of triethanolamine dispersant and 3g of dibutyl phthalate plasticizer were added, and the mixture was placed in a ball mill and ball-milled at 200rpm for 16 hours to obtain a uniformly dispersed media slurry.
[0094] (2) Casting film: The dielectric slurry is formed by casting machine, and the casting speed and doctor blade gap are controlled to form a dielectric ceramic film with a thickness of 10μm.
[0095] (3) Inner electrode printing: Nickel inner electrode paste is coated on the dielectric ceramic film by screen printing to form the inner electrode layer 3 pattern. After drying, the thickness of the inner electrode layer 3 is about 1 μm.
[0096] Among them, 50g of ultrafine nickel powder with a particle size ≤1μm, 8g of barium titanate powder, 3g of ethyl cellulose and 39g of terpineol were placed in a three-roll mill and mixed and rolled 6 times to obtain a nickel internal electrode slurry with a viscosity of 15Pa·s.
[0097] (4) Stacking and pressing: The dielectric ceramic films printed with the inner electrode layer 3 are stacked alternately, with a total of about 400 inner electrodes to form an effective electrode region; protective cover sheets are stacked on the upper and lower sides of the effective electrode region, and the protective cover sheets are made of dielectric ceramic films without printed inner electrodes, with a thickness of about 30 μm. After stacking, pressing is performed to form a block.
[0098] (5) Cutting: Use a cutting machine to cut the block into individual capacitor blanks. The blank size corresponds to the final product specification 1206, and the specific size is 3.2mm×1.6mm.
[0099] (6) Debinding and sintering: The capacitor green is debinded in an air atmosphere. Specifically, the temperature is raised to 280°C at a heating rate of 1°C / min and held for 4 hours. Then, the temperature is raised to 350°C at a heating rate of 1°C / min and held for 2 hours. Finally, the temperature is raised to 400°C at a heating rate of 1°C / min and held for 2 hours to remove the organic binder. Then, the main sintering is carried out in a N2 / H2 mixed gas at a heating rate of 2°C / min to 1220°C and held for 3 hours to densify the ceramic and simultaneously sinter the nickel inner electrode.
[0100] (7) Chamfering: The sintered ceramic body is placed in a chamfering machine, and grinding media and grinding fluid are added to perform chamfering treatment, so that the edges of the ceramic body are smooth and the dimensions are accurate, while exposing the end of the inner electrode to prepare for the subsequent coating of the outer electrode. The prepared ceramic body conforms to the 1206 specification, with specific dimensions of 3.2mm×1.6mm×1.2mm, a designed capacity of 100μF, a dielectric ceramic layer 4 thickness of 10μm, and approximately 400 electrode layers in the effective electrode area.
[0101] S2. Preparation of a protective slurry containing hollow microspheres. The steps for preparing the protective slurry include: (1) Add 80 parts by volume of fly ash cenospheres and 20 parts by volume of glass powder to 200 parts by volume of organic solvent, wherein the organic solvent is a mixture of toluene and ethanol in a volume ratio of 1:1, to form the first mixed system.
[0102] The fly ash cenospheres have a particle size of approximately 100 μm and a bulk density of 0.30 g / cm³. 3 The true density is 0.55 g / cm³. 3 The glass powder used is borosilicate glass with a softening point of approximately 600°C.
[0103] (2) Add 60.16g of binder, 12.8g of stabilizer, 12.8g of dispersant, 6.4g of plasticizer and 6.4g of stabilizer to the first mixing system in small amounts and multiple times. The total amount of the above-mentioned binder, plasticizer, stabilizer, defoamer and dispersant is 40% of the mass of organic solvent to form the second mixing system.
[0104] The binder is PVB; the stabilizer is polyethylene glycol; the dispersant is a phosphate ester dispersant, model Hostaphat OPS 75E; the plasticizer is dibutyl phthalate; and the stabilizer is polyethylene glycol.
[0105] (3) The second mixing system was ultrasonically stirred in a water bath at 60°C for 5 hours to form a uniform slurry.
[0106] S3. Secure the sintered and chamfered ceramic body at both ends using clamps. Apply the aforementioned protective slurry, ensuring it covers all four sides of the ceramic body except for the ends, guaranteeing complete coverage of the corresponding outer surface areas. Remove the ceramic body and allow it to stand at room temperature for 10 minutes, allowing excess slurry to drip off naturally and the slurry's fluidity to smooth the coating surface. Place the ceramic body coated with the protective slurry in an oven and dry at 80°C for 30 minutes to remove organic solvents. Then dry at 120°C for 2 hours to form a protective layer.
[0107] S4. Perform a first heat treatment on the protective layer. Specifically, first heat the layer to 240℃ at a heating rate of 2℃ / min and hold for 2 hours, then heat it to 350℃ at a heating rate of 1℃ / min and hold for 2 hours, then heat it to 500℃ at a heating rate of 2℃ / min and hold for 1 hour to remove adhesives and other additives, and finally heat it to 950℃ at a heating rate of 5℃ / min and hold for 1 hour, then allow it to cool naturally to room temperature. The composite protective layer 1 has a thickness of approximately 50μm.
[0108] S5. External electrodes 2 are formed at both ends of the ceramic body. Specifically, the two ends of the ceramic body are immersed in silver external electrode paste, and the immersion depth is controlled so that the silver paste is evenly attached to both ends of the ceramic body and in contact with the exposed internal electrode tip. Then, the ceramic body with silver paste is dried at 150°C for 15 minutes. Then, the dried ceramic body is subjected to a second heat treatment in air atmosphere. Specifically, the temperature is raised to 850°C at a heating rate of 5°C / min and held for 10 minutes to allow the silver paste to be fully sintered to form silver external electrodes 2. The thickness of silver external electrodes 2 is about 26μm.
[0109] The process involves taking 78g of silver powder with a particle size of 1~3μm, 5g of borosilicate glass powder, 4g of ethyl cellulose resin and 13g of terpineol solvent, mixing and rolling them 5 times in a three-roll mill to obtain a silver external electrode paste with a viscosity of 25Pa·s and a solid content of 80wt%.
[0110] S6. Electroplating is performed on the outer electrode 2 to form an outer electrode plating layer. Specifically, the ceramic body with the outer electrode 2 formed thereon is placed in the electroplating tank and electroplating is performed sequentially: (1) Electroplating of nickel layer: In nickel sulfamate plating solution, the current density is set to 2A / dm 2 The electroplating time is 60 minutes to form a nickel layer with a thickness of about 3 μm, which serves as a barrier layer to prevent silver migration.
[0111] (2) Electroplating of tin layer: In the tin methanesulfonate plating solution, the current density is set to 1.5 A / dm. 2 The electroplating time is 30 minutes, forming a tin layer with a thickness of about 5μm, which serves as a solderable layer to facilitate PCB board soldering.
[0112] After electroplating, the product is cleaned with deionized water and dried to obtain the final MLCC ceramic capacitor product with the middle part wrapped by composite protective layer 1. The finished product has a size specification of 1206 and a capacitance of 100μF.
[0113] Example 2 The difference between Example 2 and Example 1 is that fly ash cenospheres are replaced with hollow glass microspheres, wherein the median particle size D50 of the hollow glass microspheres is 45 μm and the bulk density is 0.26 g / cm³. 3 The true density is 0.55 g / cm³. 3 .
[0114] Example 3 A method for preparing a ceramic capacitor includes the following steps: S1. Take the sintered and chamfered ceramic body. The specific steps are the same as in Example 1. The ceramic body obtained conforms to the 1206 specification. The specific dimensions are 3.2mm×1.6mm×1.2mm. The designed capacity is 100μF. The thickness of the dielectric ceramic layer 4 is 10μm. The number of electrode layers in the effective electrode area is about 400.
[0115] S2. Prepare a protective slurry containing hollow microspheres. The steps for preparing the protective slurry are the same as in Example 1.
[0116] S3. Coat both ends of the ceramic body with external electrode paste and dry. Specifically, immerse both ends of the sintered and chamfered ceramic body in silver external electrode paste. The specific method is the same as in Example 1.
[0117] S4. Apply the protective slurry to all outer surface areas of the ceramic body except for the two end faces and dry it to form a protective layer. The specific method is the same as in Example 1.
[0118] S5. Perform a third heat treatment on the ceramic body containing the protective layer and the external electrode slurry, namely, co-heat treatment in an air atmosphere: heat up to 750°C at a heating rate of 5°C / min, hold for 30 min, so that the protective slurry and the external electrode slurry are sintered simultaneously to form a composite protective layer 1 and an external electrode 2, wherein the thickness of the composite protective layer 1 is about 50 μm, and the thickness of the silver external electrode 2 is about 26 μm.
[0119] Then, electroplating is performed on the outer electrode 2 to form an outer electrode plating layer. The specific steps are the same as in Example 1, resulting in the final MLCC ceramic capacitor product with the middle part wrapped by the composite protective layer 1. The finished product has a size specification of 1206 and a capacitance of 100μF.
[0120] Example 4 The difference between Example 4 and Example 3 is that fly ash cenospheres are replaced with hollow glass microspheres used in Example 2.
[0121] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the first heat treatment temperature of the composite protective layer 1, that is, the highest temperature, is 750°C; and the second heat treatment temperature of the external electrode 2 is 450°C.
[0122] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the thickness of the composite protective layer 1 is approximately 1 μm.
[0123] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the thickness of the composite protective layer 1 is approximately 300 μm.
[0124] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that 50 parts by volume of fly ash cenospheres and 50 parts by volume of glass powder were used.
[0125] Comparative Example 5 The difference between Example 5 and Example 1 is that Example 5 uses 90 parts by volume of fly ash cenospheres and 10 parts by volume of glass powder.
[0126] Comparative Example 6 The difference between Comparative Example 6 and Example 1 is that the ceramic body and external electrode 2 were prepared according to the steps of Example 1, but the composite protective layer 1 was not coated, and the MLCC product was directly electroplated to obtain the MLCC product, which corresponds to the conventional 1206 specification 100μF MLCC product.
[0127] Comparative Example 7 The difference between Comparative Example 7 and Example 1 is that hollow microspheres are not added to the protective slurry; only glass powder, solvent, and binder are used to form a dense glass protective layer.
[0128] Comparative Example 8 The difference between Comparative Example 8 and Example 1 is that the first heat treatment temperature is 500°C and the second heat treatment temperature is 850°C, that is, the sintering temperature of the composite protective layer is lower than the sintering temperature of the external electrode, and the process sequence is reversed.
[0129] Performance testing To better verify the performance of the ceramic capacitors obtained in the above embodiments and comparative examples, performance tests were performed on the ceramic capacitors prepared in the above comparative examples and embodiments.
[0130] One hundred samples of each of the ceramic capacitors prepared in Examples 1-4 and Comparative Examples 1-8 were selected for performance testing. The average value was taken after the test. The performance test included vibration failure rate, impact failure rate, high temperature welding failure rate, and howling decibel test.
[0131] The above performance indicators were all tested using existing known methods, and the specific test methods are as follows: 1. Vibration failure rate test: Referring to GB / T 2423.10-2019, the vibration duration was set to 20 minutes, and the vibration acceleration was 5g, i.e., 49m / s². 2 The vibration directions are three orthogonal directions: X-axis, Y-axis, and Z-axis. The test period is 12 vibration cycles in each direction.
[0132] The PCB board with the MLCC sample soldered on it was fixed on the vibration test bench, and sinusoidal vibrations were applied sequentially in the X, Y, and Z directions under the conditions described above. After the test, the MLCC ceramic body and solder joints were inspected for visible cracks using an optical microscope. At the same time, a capacitance meter was used to measure the change in sample capacitance. The test frequency was set to 1 kHz and the bias voltage to 0.5 V.
[0133] Failure is determined if any of the following conditions are met: (1) visible cracks appear in the ceramic body or weld; (2) the capacity change rate exceeds ±15% of the initial value.
[0134] Vibration failure rate = (number of failed vibration test samples / 100) × 100%.
[0135] 2. Impact failure rate: Referring to GB / T 2423.5-2019, the impact type is set as sinusoidal impact, the impact amplitude is 1.5mm, the impact frequency is 1055Hz, and the cumulative number of impacts is 18.
[0136] The PCB board with the MLCC sample soldered on it was fixed on the impact test bench, and a sinusoidal impact was applied under the conditions described above. After the test, the sample was checked for failure according to the same judgment criteria as the vibration test.
[0137] Impact failure rate = (number of failed impact test samples / 100) × 100%.
[0138] 3. High-temperature welding failure rate: Refer to GB / T 26930-2011, the specific test procedures are as follows: (1) Mount the MLCC sample onto the corresponding pad on the PCB board. The pad is pre-coated with solder paste, wherein the solder paste composition is Sn96.5 / Ag3.0 / Cu0.5, which conforms to the JIS-Z-3284 standard.
[0139] (2) The reflow soldering process is used for welding. The peak temperature of the reflow soldering is 255℃, the time to exceed 220℃ is 90s, the preheating rate is 1.5℃ / s, the cooling rate is 3.0℃ / s, and the temperature curve conforms to the IPC / JEDEC J-STD-020 standard.
[0140] (3) After welding, the sample is allowed to cool naturally to room temperature. The appearance of the sample is examined using an optical microscope. At the same time, the capacitance change of the sample is measured using a capacitance tester. The test frequency is set to 1kHz and the bias voltage is 0.5V. The sample is considered to have failed if any of the following conditions are met: visible cracks appear in the ceramic body; visible cracks appear in the protective layer, or the protective layer peels off or separates from the ceramic body; the sample capacitance change rate exceeds ±15% of the initial value; or the sample is found to have welding defects such as tombstoning or displacement after welding, which prevents it from being used normally. The defect judgment is based on the IPC-A-610 standard.
[0141] 4. Whistling decibel test: The test is conducted according to GB / T 12060.5-2011, using a loudspeaker or miniature sound-generating device acoustic performance testing device. The specific configuration is as follows: Test stand: An acoustic testing platform used to fix the sample to be tested and the microphone; Power amplifier: A power amplifier used to drive speakers and generate sweep excitation signals; Microphone: Sensitivity ≥50mV / Pa, frequency response range 20Hz-20kHz, conforming to IEC 61094-4 standard; Echo chamber: semi-anechoic chamber or full anechoic chamber, with ambient noise ≤20dB, conforming to GB / T 6882 standard; Sound analysis device: Audio analyzer, such as Keysight U8903B or equivalent, with spectrum analysis function; Signal generator: capable of generating continuous frequency sweep signals from 20Hz to 20kHz; Test fixture: Used to hold PCB boards with MLCC samples soldered on them.
[0142] The distance between the speaker and the PCB board under test is 5mm; the distance between the microphone and the PCB board under test, i.e., the distance between the microphone and the center of the MLCC sample, is 30mm; to avoid direct sound interference, the microphone axis and the speaker axis are at 45°~90°.
[0143] The frequency sweep range is set to 20Hz~20kHz, which can basically cover the frequency band that the human ear can hear. The frequency sweep method is continuous logarithmic sweep, the frequency sweep rate is 100Hz / s, the excitation signal type is sine wave, the excitation voltage is 1Vpp, the DC bias voltage is 2V, and the test environment temperature is 25℃±2℃. The excitation voltage and DC bias voltage can be adjusted according to the sample specifications.
[0144] The specific testing steps are as follows: (1) Solder the MLCC samples onto a dedicated test PCB board with dimensions of 50mm×50mm×1.6mm. The PCB board is made of FR-4 material and conforms to the IPC-4101 standard to ensure good soldering quality, full solder joints, and no cold solder joints. Prepare 100 samples of each type.
[0145] (2) Setup: Fix the PCB board with the MLCC sample soldered on it onto the test fixture in the anechoic chamber. Install according to the following distance parameters: The speaker is installed below or to the side of the PCB board, with the center of its sound-emitting surface 5mm away from the surface of the PCB board; the microphone is installed above the PCB board, facing the center of the MLCC sample, with the front end of the microphone 30mm away from the surface of the MLCC sample; adjust the microphone position so that the microphone axis is 90° to the speaker axis.
[0146] (3) Background noise measurement: Measure the background noise in the anechoic chamber without applying an excitation signal, and ensure that the background noise is ≤20dB. Otherwise, readjust the test environment.
[0147] (4) Frequency sweep test: Apply a 2V DC bias voltage to both ends of the MLCC sample and stabilize for 1s. Simultaneously apply a 1Vpp AC frequency sweep signal, setting the frequency sweep to 20Hz~20kHz. Use a power amplifier and speaker or conduct the signal directly through the PCB board to generate a frequency sweep sound field excitation around the sample. In the actual test, the excitation signal acts on both the MLCC sample and the speaker, jointly exciting the sample vibration. Use a microphone to collect the sound pressure signal radiated by the sample vibration, and use a sound analysis device to record the sound pressure level in the 20Hz~20kHz frequency sweep range.
[0148] (5) Data recording: Record the maximum sound pressure level throughout the frequency sweep process, in dB(A). The A-weighted curve conforms to the IEC61672-1 standard; at the same time, record the corresponding frequency at which the maximum sound pressure level occurs. 100 samples of each type are tested, and the maximum sound pressure level of each sample is recorded.
[0149] (6) Data processing: Calculate the arithmetic mean of the maximum sound pressure level of 100 samples as the howling noise value of the sample, and calculate the standard deviation to evaluate the consistency of the samples.
[0150] If any outlier occurs during the above testing process, such as exceeding the average value by 3 times the standard deviation, it should be removed and the test should be supplemented to 100 valid data points, and the average value should be taken.
[0151] The specific test results of Examples 1-4 and Comparative Examples 1-8 are shown in Table 1 and Table 2, respectively.
[0152] Table 1. Performance test results of ceramic capacitors obtained in Examples 1-4 Example 1 2% 3% 2% 33 Example 2 2% 3% 2% 35 Example 3 3% 5% 2% 42 Example 4 3% 5% 2% 44 Table 2. Performance test results of ceramic capacitors obtained from Comparative Examples 1-8 Comparative Example 1 7% 9% 5% 63 Comparative Example 2 12% 14% 7% 66 Comparative Example 3 3% 4% 22% 51 Comparative Example 4 10% 12% 6% 64 Comparative Example 5 5% 6% 15% 53 Comparative Example 6 15% 18% 8% 69 Comparative Example 7 10% 12% 6% 66 Comparative Example 8 12% 14% 7% 67 The vibration failure rate test results above show that the vibration failure rates of Examples 1-4 are all ≤3%, which meets the qualification requirements of GB / T2423.10, i.e., failure rate ≤10%, which is significantly better than Comparative Examples 1-8. This indicates that the composite protective layer 1 containing hollow microspheres can effectively absorb vibration energy and prevent cracks from forming in the ceramic body.
[0153] The impact failure rate test results above show that the impact failure rates of Examples 1-4 are all ≤5%, which meets the qualification requirements of GB / T2423.5, i.e., failure rate ≤10%, which is significantly better than Comparative Examples 1-8. This indicates that the composite protective layer 1 containing hollow microspheres has a good buffering effect on instantaneous impact stress.
[0154] The high-temperature welding failure rate test results show that the high-temperature welding failure rates of Examples 1-4 are all ≤2%, which meets the acceptance criteria of GB / T 26930 and IEC 60068-2-58, i.e., failure rate ≤5%, which is significantly better than Comparative Examples 1-8. Among them, the high-temperature welding failure rate of Comparative Example 3 is as high as 22%. This is because the excessively thick protective layer has a large thermal expansion stress during the high temperature of reflow soldering, which leads to cracking of the protective layer or peeling off from the ceramic body.
[0155] The test results above demonstrate that the present invention, by setting a composite protective layer 1 containing hollow microspheres, comprehensively improves the stress variation resistance of MLCCs from three dimensions: periodic vibration stress, instantaneous impact stress, and thermal stress. Specifically, the composite protective layer 1 containing hollow microspheres can effectively absorb periodic vibration energy, buffer instantaneous impact loads, and alleviate thermal stress during reflow soldering, thereby significantly improving the MLCC's ability to resist various stresses generated during PCB board bending, equipment drop collisions, and high-temperature soldering, thus reducing the risk of cracking and failure of the ceramic body.
[0156] As can be seen from the above whistling performance test results, the whistling noise of Examples 1-4 is 33~42dB, that is, the whistling noise of the ceramic capacitor with protective layer prepared in the present invention is ≤42dB, which is significantly better than that of Comparative Examples 1-8. This shows that the ceramic capacitor with composite protective layer 1 containing hollow microspheres prepared in this embodiment has achieved a balance and optimization in terms of reliability and noise reduction effect.
[0157] The above test results demonstrate that the present invention, by setting a composite protective layer 1 containing hollow microspheres, utilizes the friction and deformation of the hollow microspheres' cavity walls to convert vibrational mechanical energy into heat energy consumption, thus endowing MLCCs with excellent vibration damping performance and effectively suppressing howling noise. Specifically, the composite protective layer 1 containing hollow microspheres achieves excellent vibration damping effect through the cavity structure of the hollow microspheres, which can significantly reduce the transmission of vibrational energy generated by the inverse piezoelectric effect to the PCB board, thereby effectively suppressing howling noise, improving the user experience of electronic products in silent scenarios, and thus achieving a unity of reliability and comfort, that is, simultaneously achieving the dual technical effects of stress resistance and howling suppression.
[0158] As can be seen from Examples 1-4 and the corresponding test results, both distributed sintering and co-sintering schemes can significantly improve the stress resistance and squeal suppression of MLCCs. The distributed sintering scheme is slightly better than the co-sintering scheme in various performance indicators. This is because in the distributed sintering scheme, the protective layer is sintered independently, allowing for independent optimization of its sintering temperature and time, resulting in a more fully densified composite structure. Although the co-sintering scheme is slightly inferior to the distributed sintering scheme in performance, its process flow is simpler, and its energy consumption and production costs are lower, giving it a competitive advantage in large-scale production. Both schemes have their applicable scenarios and are both within the scope of protection of this invention.
[0159] As can be seen from Examples 1-2 and Comparative Example 1 and the corresponding test results, when the sintering temperature of the protective layer is too low, the low-temperature glass powder in the protective slurry fails to soften, flow, and form a continuous glass matrix, and the hollow microspheres cannot form a strong bond with the matrix material. The resulting protective layer is loose and porous, containing a large number of unmelted particles and voids, resulting in extremely weak adhesion to the ceramic substrate. Consequently, under external vibration or impact, the protective layer cannot effectively absorb and disperse stress energy, functioning only as a loosely stacked powder layer with extremely limited buffering effect. During subsequent high-temperature welding, due to insufficient interfacial bonding strength between the protective layer and the ceramic substrate, the difference in their thermal expansion coefficients generates significant interfacial thermal stress under high-temperature conditions, leading to cracking or even complete peeling of the protective layer. This reduces product reliability and significantly increases the high-temperature welding failure rate of the components.
[0160] In contrast, Examples 1-2, by setting a suitable sintering temperature, allow the glass powder to fully melt, and the hollow microspheres to form a strong composite structure with the matrix, thereby enabling them to perform their functions of buffering stress and suppressing howling, while ensuring reliability in the subsequent welding process.
[0161] As can be seen from Examples 1-2 and Comparative Example 2 and the corresponding test results, the protective layer of Comparative Example 2 is too thin and cannot effectively absorb and disperse mechanical stress and vibration energy, and its performance is close to that of products without a protective layer.
[0162] As can be seen from Examples 1-2 and Comparative Example 3 and the corresponding test results, the protective layer of Comparative Example 3 is too thick. The excessively thick protective layer generates huge thermal stress under the high temperature of reflow soldering, which causes the protective layer itself to crack or peel off from the ceramic body, thus worsening the heat resistance of soldering.
[0163] As can be seen from Examples 1-2 and Comparative Example 4 and the corresponding test results, the amount of hollow microspheres used in Comparative Example 4 was too small, making the protective layer approximately as dense as glass. It lacked sufficient hollow structure for buffering and energy absorption, resulting in a significant reduction in the stress resistance and noise reduction effect of the component.
[0164] As can be seen from Examples 1-2 and Comparative Example 5 and the corresponding test results, the amount of hollow microspheres used in Comparative Example 5 was too high, resulting in an excessively high porosity and loose structure in the protective layer. This made it prone to collapse under high welding temperatures, and significantly reduced the mechanical strength and heat resistance of the protective layer.
[0165] As can be seen from Examples 1-2 and Comparative Example 6 and the corresponding test results, Comparative Example 6 did not have a protective layer, which resulted in the ceramic body being directly exposed. Cracks were easily initiated and propagated under external force, and the reverse piezoelectric vibration was directly transmitted to the PCB board, resulting in a very serious howling problem.
[0166] As can be seen from Examples 1-2 and Comparative Example 7 and the corresponding test results, Comparative Example 7 did not use hollow microspheres, resulting in a pure glass structure for the protective layer. The pure glass layer is a rigid structure, lacking elastic buffering, and cannot convert the mechanical energy of vibration into heat energy, thus having limited effect on suppressing stress and howling.
[0167] It can be seen from Examples 1-2 and Comparative Example 8 and the corresponding test results that the sintering temperature of the protective layer in Comparative Example 8 was insufficient, resulting in incomplete sintering of the protective layer, weak bonding with the ceramic body, and easy peeling or cracking under external force.
[0168] In summary, this invention addresses the common industry problems of poor stress resistance in ceramic capacitors prepared by existing technologies, such as poor resistance to bending during welding, resistance to external impacts, scratches, and pressure during use, and the tendency to cause howling and affect use. By adding a composite protective layer 1 to the ceramic body of the ceramic capacitor, the stress resistance of the finished product is improved. At the same time, by utilizing the sound absorption and sound insulation capabilities of the hollow microspheres in the composite protective layer 1, the howling volume of the ceramic capacitor during use is significantly reduced, which has excellent practical application significance.
[0169] In the above embodiments, the descriptions of each embodiment have different focuses. For parts not described in detail in a certain embodiment, please refer to the relevant descriptions in other embodiments.
[0170] The ceramic capacitor and its preparation method and apparatus provided in the embodiments of this application have been described in detail above. Specific examples have been used to illustrate the principles and implementation methods of this application. The description of the above embodiments is only for the purpose of helping to understand the technical solutions and core ideas of this application. Those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. These modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
Claims
1. A ceramic capacitor with a protective layer, comprising: A ceramic body, the ceramic body including an effective electrode region; wherein, the effective electrode region includes a plurality of inner electrode layers and a plurality of dielectric ceramic layers, the inner electrode layers and the dielectric ceramic layers being alternately stacked; Two external electrodes are respectively disposed on two opposite end faces of the ceramic body along its length direction, and are electrically connected to the corresponding internal electrode layers, characterized in that... The ceramic capacitor also includes a composite protective layer, which covers the entire outer surface area of the ceramic body except for the two end faces. The composite protective layer comprises dispersed hollow microspheres.
2. A ceramic capacitor with a protective layer according to claim 1, characterized in that, The hollow microspheres are hollow glass microspheres or hollow ceramic microspheres; The hollow microspheres have a closed or semi-closed cavity structure inside.
3. A ceramic capacitor with a protective layer according to claim 1, characterized in that, The hollow microspheres have a particle size of 1~150μm.
4. A ceramic capacitor with a protective layer according to claim 1, characterized in that, The bulk density of the hollow microspheres is 0.06~0.50 g / cm³. 3 .
5. A ceramic capacitor with a protective layer according to claim 1, characterized in that, The true density of the hollow microspheres is 0.1~1.5 g / cm³. 3 .
6. A ceramic capacitor with a protective layer according to claim 1, characterized in that, The thickness of the composite protective layer is 5~200μm.
7. A ceramic capacitor with a protective layer according to claim 1, characterized in that, The thickness of the composite protective layer is h, and the thickness of the ceramic body in the stacking direction is H, satisfying: 0.02≤h / H≤0.
15.
8. A method for preparing a ceramic capacitor with a protective layer as described in any one of claims 1-7, characterized in that, Includes the following steps: S11. Take a sintered and chamfered ceramic body. The ceramic body includes an effective electrode region. The effective electrode region includes several inner electrode layers and several dielectric ceramic layers. The inner electrode layers and the dielectric ceramic layers are stacked alternately. S12. Prepare a protective slurry containing hollow microspheres; S13. The protective slurry is applied to all the outer surface areas of the ceramic body except for the two end faces and dried to form a protective layer. S14. Perform a first heat treatment on the protective layer to obtain a ceramic body containing a composite protective layer; S15. Apply an external electrode paste to the area where the two end faces of the ceramic body are located, and form an external electrode after a second heat treatment, thereby obtaining a ceramic capacitor with a protective layer. Wherein, the temperature of the first heat treatment is higher than the temperature of the second heat treatment, and the temperature of the first heat treatment is lower than the sintering temperature of the ceramic body in S11.
9. A method for preparing a ceramic capacitor with a protective layer as described in any one of claims 1-7, characterized in that, Includes the following steps: S21. Take a sintered and chamfered ceramic body. The ceramic body includes an effective electrode region. The effective electrode region includes several inner electrode layers and several dielectric ceramic layers. The inner electrode layers and the dielectric ceramic layers are stacked alternately. S22. Prepare a protective slurry containing hollow microspheres; S23. Apply external electrode paste to the areas where the two end faces of the ceramic body are located and dry it; S24. The protective slurry is applied to all the outer surface areas of the ceramic body except for the two end faces and dried to form a protective layer. S25. Perform a third heat treatment on the ceramic body containing the protective layer and the external electrode paste to obtain a ceramic capacitor with a protective layer. The temperature of the third heat treatment is lower than the sintering temperature of the ceramic body in S21.
10. A method for preparing a ceramic capacitor with a protective layer according to claim 8 or 9, characterized in that, The steps for preparing the protective slurry include: Hollow microspheres and matrix material are added to an organic solvent to form a first mixed system; an additive is added to the first mixed system to form a second mixed system; the second mixed system is ultrasonically stirred in a water bath at 50℃~70℃ for 4~6 hours to form a uniform slurry. The volume ratio of the hollow microspheres to the matrix material is (3.7~17):3; The volume ratio of the total volume of the hollow microspheres and the matrix material to the volume of the organic solvent is 3:(5~6); The amount of the additive is 40% of the mass of the organic solvent, and the additive is selected from one or more of binders, plasticizers, stabilizers, defoamers, and dispersants.
Citation Information
Patent Citations
Ceramic capacitor and preparation method thereof
CN121790170A
Conductive paste composition for external electrode and multilayer ceramic electronic component including the same
CN104299677A
Low-howling multilayer ceramic dielectric capacitor, preparation method thereof and end sealing tool
CN120183909A